(untitled) (Third Sector Social Economic Review, 2020)
In Turkey, cities, as a result of non-planned and rapid urbanization, break down by the reasons such as economical inadequacies which comes first at the list, and social unconsciousness, over population, inadequate infrastructure. Urban transformations arise in an attempt to improve this collapse. Urbanization is a process needed to create a modern life style, a strong urban economy and up to date urban areas. The urbanization projects are arranged for the cities need reparation. These are the projects based on the desire of the government and private sector and the plans of the municipality. Nowadays, the urban transformation projects occur by several applications. Its main aim is to provide public benefit. Aiming the public benefit provides so many advantages (such as buying lands, making contracts) for the municipality. Confliction of the personal benefit and public benefit brings up a new problem called urban annuity and this completely brings a different aspect for the urbanization. As one of the important metropolitan cities of Turkey, Konya Metropolitan Municipality has also performed very successful urban transformation projects. Meram Municipality named “Green Meram” also shared the success of these projects. “Altın Hamle” and “Çaybaşı” projects aim the reinforcement of urban structure and rehabilitation of the living areas in Meram, Konya